Progress in investigating the relationship between Schlafen5 genes and malignant tumors - Tu, Teng; Yuan, Ye; Liu, Xiaoxue; Liang, Xin; Yang, Xiaofan; Yang, Yue (Frontiers in Oncology, 2023)
The Schlafen5(SLFN5) gene belongs to the third group of the Schlafen protein family. As a tumor suppressor gene, SLFN5 plays a pivotal role in inhibiting tumor growth, orchestrating cell cycle regulation, and modulating the extent of cancer cell infiltration and metastasis in various malignancies.However, the high expression of SLFN 5 in some tumors was positively correlated with lymph node metastasis, tumor stage, and tumor grade . This article endeavors to elucidate the reciprocal relationship between the SLFN5 gene and malignant tumors, thereby enhancing our comprehension of the intricate mechanisms underlying the SLFN5 gene and its implications for the progression, invasive potential, and metastatic behavior of malignant tumors.At the same time, this paper summarizes the basis of SLFN 5 as a new biomarker of tumor diagnosis and prognosis, and provides new ideas for the target treatment of tumor.